2013
DOI: 10.1021/ja402740q
|View full text |Cite
|
Sign up to set email alerts
|

Pd-Catalyzed Asymmetric Allylic Alkylation of Pyrazol-5-ones with Allylic Alcohols: The Role of the Chiral Phosphoric Acid in C–O Bond Cleavage and Stereocontrol

Abstract: The combination of a palladium complex with a chiral phosphoramidite ligand and a chiral phosphoric acid enables the first highly efficient asymmetric allylic alkylation of pyrazol-5-ones with allylic alcohols, affording multiply functionalized heterocyclic products in high yields with excellent enantioselectivities that would be of great potential in the synthesis of pharmaceutically interesting molecules.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
54
0
4

Year Published

2014
2014
2021
2021

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 195 publications
(58 citation statements)
references
References 53 publications
0
54
0
4
Order By: Relevance
“…They demonstrated the combined use of a palladium/chiral phosphoramidite ligand 61 and chiral phosphoric acid 60 to achieve highly enantioselective allylic alkylation of pyrazol-5-ones 58 with allylic alcohols (Scheme 13). 17 The reaction afforded highly functionalized heterocyclic products 59 in high yields with excellent ee's. Mechanistically, the reaction is believed to be initiated with the activation of allyl alcohols by hydrogen bonding with phosphoric acid (cf.…”
Section: Scheme 1 Rh/pd Catalyzed Enantioselective Allylic Alkylatiomentioning
confidence: 98%
“…They demonstrated the combined use of a palladium/chiral phosphoramidite ligand 61 and chiral phosphoric acid 60 to achieve highly enantioselective allylic alkylation of pyrazol-5-ones 58 with allylic alcohols (Scheme 13). 17 The reaction afforded highly functionalized heterocyclic products 59 in high yields with excellent ee's. Mechanistically, the reaction is believed to be initiated with the activation of allyl alcohols by hydrogen bonding with phosphoric acid (cf.…”
Section: Scheme 1 Rh/pd Catalyzed Enantioselective Allylic Alkylatiomentioning
confidence: 98%
“…The stereocontrol was sensitive to the substituent at the C-3 position of the pyrazol-5-one (Table 3). 19 Jiang and Xia disclosed a Brønsted acid accelerated Pd-catalyzed asymmetric allylic alkylation of azlactones using a Pd 2 (dba) 3 catalyst, Trost ligand L2 and benzoic acid. 19 Based on HRMS studies, Gong and co-workers proposed a mechanism to explain the excellent stereocontrol (Scheme 7).…”
Section: Transition Metal-catalyzed Allylic Substitution Reactions Wimentioning
confidence: 99%
“…This suggested that the BF 3 generated throughout the reaction (as observed via 19 F NMR spectroscopy) was essential for reaction activity i.e. In the absence of any Lewis acid, no silylation occurred; the only product obtained was the deuterated allyl ether 29.…”
Section: View Article Onlinementioning
confidence: 99%
“…[16] Recently,G ong and co-workers reported an AAA reaction of pyrazol-5-ones with allylic alcohols catalyzed by the combination of ap alladium complex and ac hiral phosphoric acid, [17] thus indicating that chiral phosphoric acid could act as good activator for carbonyl compounds. [16] Recently,G ong and co-workers reported an AAA reaction of pyrazol-5-ones with allylic alcohols catalyzed by the combination of ap alladium complex and ac hiral phosphoric acid, [17] thus indicating that chiral phosphoric acid could act as good activator for carbonyl compounds.…”
mentioning
confidence: 99%